On continuity of KC-functions with values in Ceder plane - Maslyuchenko, V.K.; Myronyk, O.D. (Carpathian Mathematical Publications, 2014)
We show that the Ceder plane M is a σ-metrizable space, which does not have a development. For every quasicontinuous mapping f:X→M the continuity point set C(f) is residual. We investigate the continuity point set C(f) of a mapping f:X× Y→ M, which is quasicontinuous with respect to the first variable and continuous with respect to the second one.